Work-Family Boundaries in the Digital Age: A Study in France on Technological Intrusion, Work-Family Conflict, and Stress - Giunchi, Marianna; Peña-Jimenez, Marco; Petrilli, Sara (La Medicina del Lavoro, 2023)
Background: Since previous studies have shown that the request of off-work technology-assisted supplemental work (off-TASW) can contribute to blurring the boundaries between the work and family domain by increasing work- family conflict (WFC), the purpose of this study is to go further, investigating how this relationship impacts stress perceptions. Method: A cross-sectional study that involved a sample of 221 French workers was carried out using a self-reported questionnaire. The data collected were analyzed by IBM SPSS 25.0 software, and a mediation model was tested. Results: The results showed that off-TASW was associated with higher levels of WFC (b=.32; p=.000), which was in turn associated with stress perceptions (b=.42; p=.000). Conclusions: This study contributes to un- derstanding how the intrusion of technologies during off-work times impacts workers’ perceptions of psychological wellbeing through work-family conflict. These findings should encourage the debate on the risks of staying connected to work through technologies during off-work and leisure time and stimulate the promotion of campaigns to make workers aware of their right to disconnection, to the benefits of detachment from work and recovery experiences.